2016
DOI: 10.1111/ggi.12764
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the numbers of drugs administered to elderly in‐patients with polypharmacy by a multidisciplinary review of medication using electronic medical records

Abstract: Multidisciplinary medication review using electronic medical records could significantly reduce the numbers of drugs taken by elderly inpatients receiving polypharmacy, including drugs associated with falls, in both fallers and non-fallers Geriatr Gerontol Int 2017; 17: 653-658.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…As expected, our review of all medicated subjects led to a reduction of prescriptions (an average of one drug per subject, especially psychotropic medication). In concurrence with recent studies ( 36 ), the reduction was more effective in patients receiving polypharmacy than those who were not.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, our review of all medicated subjects led to a reduction of prescriptions (an average of one drug per subject, especially psychotropic medication). In concurrence with recent studies ( 36 ), the reduction was more effective in patients receiving polypharmacy than those who were not.…”
Section: Discussionsupporting
confidence: 89%
“…Intervention studies which focused on reducing polypharmacy among older persons either with the involvement of a pharmacist or a multidisciplinary team, have largely reported significant improvements in the quality of medication use [1215]. Few studies have extended such observation to include health outcomes, but the findings have not been consistent [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Neuromuscular diseases include central and peripheral nervous system disorders, and a number of drugs, including anti‐epileptics, corticosteroids, immunoglobulins, anticoagulant agents and antipsychotics, are used for therapy. In addition, patients with these diseases often suffer a number of comorbid disorders, as a result many of these patients tend to receive multidrug therapy . Thuermann et al reported that 18.7% of neurology ward patients experienced two or more ADR during the hospitalization period .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with these diseases often suffer a number of comorbid disorders, as a result many of these patients tend to receive multidrug therapy. 10 Thuermann et al reported that 18.7% of neurology ward patients experienced two or more ADR during the hospitalization period. 11 However, there have been just a few reports on the occurrence of ADR Accepted for publication 24 January 2018.…”
Section: Introductionmentioning
confidence: 99%